EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DIPADU NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA POKOK BAHASAN HIDROKARBON KELAS XI MIA MAN 2 PEKANBARU - Regi Antina; Jimmi Copriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determite the effctivennes The Application Of The Problem Based Learning Model Combined With Numbered Head Together (Nht) Towards Student Learning Outcomes On The Subject Of Class Hydrocarbons XI MIA MAN 2 Pekanbaru . This type of research is an experimental study using design cluster randoming sampling by using research design randomized control group Pretestposttest. The research sample consistend of 3 classes, Class X1 as an experimental class 1 (Applied Problem Based Learning Combined With Numbered Head Together), Class X2 as an experimental class 2 (Problem Based Learning) and X3 as a control class (Scientific Approach). The data analysis technique used is the one-way ANOVA if there are differences, The schfee double comparison test is continued. Based on data analisis test obtained Fcount > Ftable that is 27,06 > 3,10, this means that there are significant differences in student learning outcomes at Effectivennes The Application Of The Problem Based Learning Model Combined With Numbered Head Together Outcomes On The Subject Of Class Hydrocarbons XI MIA MAN 2 Pekanbaru. Advanced test results to see significant differences in learning outcomes using the schfee double comparison test, namely the difference between the average clas and schfee values, it was found that between the classes was significantly different. Key Words: Problem Based Learning Combined With Numbered Head Together, Problem Based Learning, learning outcomes, Hydrocarbons